If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1(x + -2) = 3 Reorder the terms: 11 + -1(-2 + x) = 3 11 + (-2 * -1 + x * -1) = 3 11 + (2 + -1x) = 3 Combine like terms: 11 + 2 = 13 13 + -1x = 3 Solving 13 + -1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1x = 3 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 3 + -13 -1x = 3 + -13 Combine like terms: 3 + -13 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 |